Community-Based Home Energy Tune-Up/Audit Programs: A Step-by-Step Guide to Creating and Implementing Energy Equity Programs in Your Community - Alane Humrich; Lee Hayes Byron; Jennison Kipp; Marianne Schmink; Kimberly Davis; Paul Monaghan (EDIS)
This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication is part of a series showing how Extension agents, community activists and sustainability educators can implement a program that reduces energy use and saves money on utility expenses for low-income households. This document outlines the basic steps a team would need to complete in order to have an effective energy tune-up/audit program that is based on community needs and input. It uses programs in Alachua and Sarasota Counties to provide examples of two different approaches to achieving the same goals. https://edis.ifas.ufl.edu/wc408